Comparative study of recurrence after pterygium excision with conjunctival autografting and amniotic membrane transplantation - Kalpna Jain; J.M. Murlimanohar; Payal Garg; Muhammed Nadeem; Saroj Sarowa (International Journal of Medical Research and Review, 2016)
Introduction: Pterygium is ocular surface lesion thought to originate from damage to limbal stem cells by chronic ultra violet light exposure. It has high recurrence rates following resection. Both amniotic membrane and conjunctival autograft are source of stem cells. We compare recurrence after pterygium excision with conjunctival autografting and amniotic membrane grafting.Methods: Prospective case study of seventy patients after pterygium excision with Amniotic membrane transplantation or Conjunctival autografting. Thirty five patients divided in each group and fibrin glue used for both Amniotic membrane transplantation and Conjunctival autografting.Results: Six follow up from first postoperative day to one year were done in each group. Group A (Amniotic membrane transplantation) had less Post operative complaints. In group A, all patients have well placed graft while in group B (conjunctival autografting) nine patients have graft displacement on first post operative day. It was statistically significant (p value 0.001). The recurrence occurring four patients in group A (11.42%) while in 7 patients in group B (20%). The recurrence was more in group B although it was statistically insignificant (p value <0.511). Amniotic membrane transplantation with fibrin glue having less postoperative complaints, better graft stability and less recurrence as compare to conjunctival autografting.Conclusion: Our study shows good outcome with Amniotic membrane transplantation. Probably this is because of anti- inflammatory property of amniotic membrane, minimum surgical trauma and uniform thickness of graft.